Cardiothoracic Surgical Procedures and Techniques A Practical Manual - Molina, J. Ernesto (Springer International Publishing, 2018)
Significant changes have taken place in the realm of cardiac, thoracic, and vascular surgery during the last five to ten years. Many new operative procedures have been developed which remain relatively unknown to cardiothoracic surgeons. This practical manual covers a wide variety of these new processes, several of which are interventions offered to cardiologists practicing in the field of electrophysiology who are unaware that these interventions exist and can help them in situations they cannot solve. It includes general practical techniques; cardiac, thoracic, and vascular surgery procedures; and advances in cardiology and electrophysiology. Throughout the book, illustrations accompany the technical descriptions and show in step-by-step detail how to perform the operations and various procedures using proper equipment. Cardiothoracic Surgical Procedures and Techniques: A Practical Manual is an essential resource for physicians and related professionals, residents, fellows, physician assistants (PA), and graduate students in cardiology, cardiac surgery, thoracic surgery, and vascular surgery.